HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SERVIS BAWAH PADA EKSTRAKURIKULER BOLAVOLI PUTRA SEKOLAH MENENGAH PERTAMA NEGERI 4 BATANG ANAI - Sapitri, Nadia; Astuti, Yuni; Damrah; Sepriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the underhand serve ability of male volleyball extracurricular students of SMP Negeri 4 Batang Anai which is not optimal. This study aims to determine the relationship between arm muscle strength and hand-eye coordination with underhand serve ability, with the underhand serve ability of male volleyball extracurricular students of SMP Negeri 4 Batang Anai. This type of research is quantitative correlational. The population in this study were all male students who participated in volleyball extracurricular at SMP Negeri 4 Batang Anai, totaling 21 people, and samples were taken using total sampling technique. The instrument for arm muscle strength used push-up test, hand-eye coordination used Hand Eye Coordination Test, and underhand serve ability used AAHPER Serving Accuracy Test. The data analysis technique used Pearson product moment correlation, t test, multiple correlation, and F test. The results of the study showed that: (1) there is a significant relationship between arm muscle strength and underhand service ability with a calculated r_value of 0.44 > r_table 0.433 (2) there is a significant relationship between eye-hand coordination and underhand service ability with a calculated r_value of 0.45 > r_table 0.433 (3) there is a significant relationship between arm muscle strength and eye-hand coordination together with underhand service ability with a calculated R_value of 0.54 > r_table 0.433 and F_count 3.97 > F_table 3.52